2019
DOI: 10.5430/ijhe.v8n1p19
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Local Dances on Prospective Physical Education Teachers’ Attitudes towards the Folk Dance Course

Abstract: In this study, the effect of various local dances on prospective physical education teachers' attitudes towards the folk dance course was examined. The research was conducted by using an experimental design with pre-test/post-test control group. A total of 46 female students, which includes an experimental group consisting of 23 students attended the folk dance class and a control group consisting of 23 students did not attend the folk dance class, who are studying at Niğde Ömer Halisdemir University, School o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
4
0
3
Order By: Relevance
“…Four prismatic reflectors optical system imaging is more complex; the upper and lower prism size, bevel angle, relative distance, and camera installation position directly affect the sensor field of view range, working distance, measurement accuracy, size, and other key indicators. The upper and lower prism size and bevel angle and the scope of the public field of view, shape, and measurement distance are closely related, and inappropriate parameter settings may lead to an insufficient field of view or no public field of view; upper and lower prism relative distance directly affects the baseline distance and sensor volume, inappropriate distance will lead to reduced accuracy, and the sensor structure is large and redundant; camera installation position affects the proportion of the imaging area reasonably [21]. The reasonable placement of the camera can make the field of view increased and the measurement accuracy improved.…”
Section: Folk Dance Movement Recognition Based On Single-camera Omnid...mentioning
confidence: 99%
“…Four prismatic reflectors optical system imaging is more complex; the upper and lower prism size, bevel angle, relative distance, and camera installation position directly affect the sensor field of view range, working distance, measurement accuracy, size, and other key indicators. The upper and lower prism size and bevel angle and the scope of the public field of view, shape, and measurement distance are closely related, and inappropriate parameter settings may lead to an insufficient field of view or no public field of view; upper and lower prism relative distance directly affects the baseline distance and sensor volume, inappropriate distance will lead to reduced accuracy, and the sensor structure is large and redundant; camera installation position affects the proportion of the imaging area reasonably [21]. The reasonable placement of the camera can make the field of view increased and the measurement accuracy improved.…”
Section: Folk Dance Movement Recognition Based On Single-camera Omnid...mentioning
confidence: 99%
“…It is thought that this difference is caused by the previous experience of students regarding folk dance course participation and it is possible that the individuals who attended the course before were in a more positive mood towards folk dances. Altun & Atasoy (2019), in their study with 46 students, reported that 23 students in the experimental group who took Folk Dance course had a negative attitude towards Folk Dances before attending the lesson, but their negative attitudes have changed to positive after completing the course.…”
Section: Discussionmentioning
confidence: 99%
“…Ez a hipotézis viszont nem igazolódott be, mivel a 69 cikk alapján a kortárs tánc volt a leggyakrabban vizsgált táncműfaj (Baran, 2020;DiPasquale & Roberts, 2022;Higdon, 2022;Dryburgh, 2020;Dryburgh & Jackson, 2016;Higdon & Stevens, 2017;Kearns, 2016;O'Leary et al, 2019;Papp-Danka & Lanszki, 2020;O'Leary et al, 2019;Pulinkala 2014;Rimmer, 2017;Ritchie & Brooker, 2018;Salcedo et al, 2017;Szászi & Szabó, 2021;Salcedo et al, 2017;Tsompanaki, 2014;Walker, 2019), a klasszikus balett pedig csak a harmadik legkutatottabb terület az elmúlt évtized kutatásaiban (Barton & Ryan, 2014;Duffy, 2018;Papp-Danka & Lanszki, 2020;Petsilas et al, 2019;Rimmer, 2017;Ritchie & Brooker, 2020;Salcedo et al, 2017;Szászi & Szabó, 2021;Salcedo et al, 2017;Walker, 2019) (2. ábra). A néptánc volt a második legtöbbet kutatott táncműfaj (Altun & Atasoy, 2019;Assandri, 2019;Clendinning, 2022;Conner, 2021;Dilek, 2017;Jin & Martin, 2019;Kaktusz, 2020;Liu, 2020;Papp-Danka & Lanszki, 2020;Salcedo et al, 2017;Szászi & Szabó, 2021), a társastáncokkal kapcsolatos kutatások pedig alulreprezentáltak a mintánkban, ugyanis csak hat viz...…”
Section: Táncműfajok a Tánccal Kapcsolatos Felsőoktatási Kutatásokokbanunclassified